The Impact of Driving Restrictions on People with Epilepsy in Ireland - Klaus, Stephen P. (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Driving restrictions have a significant impact on patients with epilepsy and their families. This is documented in international studies but underreported in an Irish context. The goal of this study was to examine this impact on an Irish-based tertiary hospital cohort. Patients were recruited through the Beaumont Hospital neurology service after having been informed of a driving restriction due to an epileptic seizure. Interviews were conducted by phone, using a standardized proforma. Our analysis included 23 patients interviewed (female 65%, mean age: 45.8 years). Forty-eight percent of patients (n=11) had received a driving restriction for the first time, following a new diagnosis of epilepsy. 96% of patients (n=22) identified a car as their primary mode of transport prior to driving restriction, with one patient (n=1) using public transport. During restriction, 60% (n=14) continued to be dependent on use of a personal car driven by a friend or family member. 13% of patients (n=3) switched from primary personal car use to public transport. 83% percent (n=19) reported some access to public transport. 35% percent (n=8) of patients reported that their transportation options were limited by cost, while 55% percent (n=11) reported being negatively affected financially with 17% percent (n=3) were forced to give up their job. 13% (n=3) reported a negative impact on the doctor-patient relationship, with one patient seeking a second opinion. 9% of patients, (n=2) reported driving during the period of restriction. Quality of life and subjective happiness scores were compared across subgroups, although significance was not observed. A personal car is the primary mode of transport in this cohort both before and after driving restriction. The majority of patients adhered to the law and did not report a breakdown in the relationship with their doctor. Access and cost of public transport, reliance on family and financial loss are significant factors affecting patients.
APPROVED